Sobrecarga de opções : uma revisão meta-analítica e avaliação de potenciais moderadores - Meurer, Aline Mara (2020)
Although evidence that large sets of options may be harming to consumer choice has been widely discussed in the marketing and psychology literature, a cohesive understanding of the background and consequences of overloading choices remains under debate. Understanding the impact of overload on the internal and behavioral aspects of consumers is still considered a challenge for many researchers. This meta-analysis, using 112 observations and a set of 13.156 participants, extracted from studies carried out between the years 2000 and 2019, sought to verify the effect of the size of the option sets on the choice overload, considering the different dependent measures used in individual studies carried out, as well as to evaluate potential moderators of the relation size of the sets and overload of choices. The results showed that the greatest effects of overload are found in the relationship of the sizes of the sets with the regret and complexity of the choice. The analysis of moderations in overload was performed using satisfaction as a dependent variable, since it was the most recurrent measure in individual studies and presented significant heterogeneity between the observations. The methodological moderators "classification of journals" and type of sample (real or hypothetical) had no effect on the relationship of the extension of the sets with satisfaction. Among the theoretical moderators investigated, (classification of goods in terms of products and services; characterization of goods in terms of utility or hedonic; level of perceived risk, level of involvement and culture), only culture was significant in the relationship, demonstrating that consumers in Easterners countries are more impacted by the larger sets of alternatives than consumers in Western countries. Considering these results, academic and managerial implications were discussed, as well as limitations and recommendations for future researches.